2004
DOI: 10.1158/1535-7163.291.3.3
|View full text |Cite
|
Sign up to set email alerts
|

Antiproliferative effect of nitrosulindac (NCX 1102), a new nitric oxide-donating non-steroidal anti-inflammatory drug, on human bladder carcinoma cell lines

Abstract: Non-steroidal anti-inflammatory drugs (NSAIDs) are potent antitumoral agents but their side effects limit their clinical use. A novel class of drugs, nitric oxide-donating NSAIDs (NO-NSAIDs), was found to be safer and more active than classical NSAIDs. This study explored the effect of the NO-donating sulindac derivative, NCX 1102, on three human urothelial epithelial carcinoma cell lines (T24, 647V, and 1207) and primary cultures of normal urothelial cells. Cytotoxicity, antiproliferative effect, cell cycle a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…Numerous investigations have proven the ability of NO to prevent the proliferation of various types of cancer cells, as evidenced by studies [ 79 , 80 , 81 , 82 , 83 ]. One particularly promising substance, known as GIT-27NO, serves as a source of NO and has demonstrated the ability to prevent the growth of prostate cancer cells (PC3 and LnCap) in a dose-dependent manner, as shown in experiments performed on mice without functional immune systems [ 84 ].…”
Section: Repurposing Levosimendan For Oncologymentioning
confidence: 99%
“…Numerous investigations have proven the ability of NO to prevent the proliferation of various types of cancer cells, as evidenced by studies [ 79 , 80 , 81 , 82 , 83 ]. One particularly promising substance, known as GIT-27NO, serves as a source of NO and has demonstrated the ability to prevent the growth of prostate cancer cells (PC3 and LnCap) in a dose-dependent manner, as shown in experiments performed on mice without functional immune systems [ 84 ].…”
Section: Repurposing Levosimendan For Oncologymentioning
confidence: 99%
“…NO can alter the expression of genes involved in DNA repair and tumor suppression, as well as affect processes such as apoptosis and metastasis [68]. Studies have shown that NO can inhibit the growth of various cancer cells, including gastric [69], breast [70], prostate [71], and bladder cancer cells [72], as well as neural precursor cells [73]. GIT-27NO, a novel NO donor, has been shown to inhibit the growth of PC3 and LnCap prostate cancer cells in a concentration-dependent manner when xenografted into nude mice [74].…”
Section: Nitric Oxide (No) Releasementioning
confidence: 99%
“…The combination of NO and ionizing radiation can also induce apoptotic cell death by activating the p53 pathway. In one study, treating colorectal cancer cells with NO donors resulted in a significant increase in the radiosensitivity of the Studies have shown that NO can inhibit the growth of various cancer cells, including gastric [69], breast [70], prostate [71], and bladder cancer cells [72], as well as neural precursor cells [73]. GIT-27NO, a novel NO donor, has been shown to inhibit the growth of PC3 and LnCap prostate cancer cells in a concentration-dependent manner when xenografted into nude mice [74].…”
Section: Nitric Oxide (No) Releasementioning
confidence: 99%
“…Delivery methods include nitric oxide donor drugs and iNOS gene transfer that can achieve concentrations of NO ⋅ in the micromolar range. This lead to apoptosis in a wide variety of human cancer cells including bladder (132)(133)(134) breast (135), colon (136,137), pancreas (138,68) and prostate (139). There is also some evidence that NO ⋅ mediated apoptosis may show some selectivity for transformed compared with normal cells (fibroblasts) and that this can be attributed to increased superoxide production in transformed cells leading, on interaction with NO ⋅ , to peroxynitrite production (51).…”
Section: Enhancing Nitrosative Stress For Therapeutic Benefitmentioning
confidence: 99%